The effect of nuclear gas distribution on the mass determination of supermassive black holes. (January 2018) - Mejía-Restrepo, J.; Lira, P.; Netzer, H.; Trakhtenbrot, B.; Capellupo, D.
Abstract Supermassive black holes reside in the nuclei of most galaxies. During their active episodes, black holes are powered by accretion discs where gravitational energy is converted into radiation1 . Accurately determining black hole masses is key to understand how the population evolves over time and how the black holes relate to their host galaxies2–4 . Beyond the local universe, z  ≳  0.2, the mass is commonly estimated assuming a virialized motion of gas in the close vicinity of the active black holes, traced through broad emission lines5, 6 . However, this procedure has uncertainties associated with the unknown distribution of the gas clouds. Here, we show that the black hole masses derived from the properties of the accretion disk and virial mass estimates differ by a factor that is inversely proportional to the width of the broad emission lines. This leads to virial mass misestimations up to a factor of six. Our results suggest that a planar gas distribution that is inclined with respect to the line of sight may account for this effect. However, radiation pressure effects on the distribution of gas can also reproduce our results. Regardless of the physical origin, our findings contribute to mitigating the uncertainties in current black hole mass estimations and, in turn, will help us to better understand the evolution of distant supermassive black holes and their host galaxies. Black hole masses derived from the properties of the accretion disk and virial mass estimates differ by a factor that is inversely proportional to the width of the broad emission lines. An inclined planar gas distribution may account for this effect.